Effectiveness of Virgin Coconut Oil and Virgin Olive Oil on Perineal Laceration - Asiyah, Nor; Risnawati, Indah; Khoirunnisa', Fania Nurul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Perineal massage is one of the way to reduce maternal morbidity and reduce the risk of bleeding caused by laceration of the perineum. Not only Virgin Olive Oil, but also Virgin Coconut Oil becomes the alternative thing that easily absorbed by the skin. This study aims to examine the effect of Virgin Coconut Oil and Virgin Olive Oil on perineal massage on the degree of perineal laceration. This research was Quasi experimental designs, with the subjects were pregnant women with gestational age ≥34-35 weeks. The data used the Mann-Whitney test and tested 2 proportions to assess the effectiveness of the essential oils used. The result showed that there was influence of perineal massage with perineal laceration (p <0,05). Therefore, there is influence of VCO and VOO on perineal massage against the perineal laceration event. Further research is needed to assess the determinants of perineal laceration with different variables or interventions.